2018
DOI: 10.18182/tjf.429499
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different hormone doses on rooting of Berberis thunbergii 'Atropurpurea Nana' cuttings

Abstract: Özet: Anavatanı Japonya olan Berberis thunbergii 'Atropurpurea Nana', düzgün formu, gösterişli bordo yaprakları ile özellikle gruplar halinde kullanımıyla peyzaj mimarlığı uygulama alanlarında oldukça etkilidir. Görsel özelliklerinin yanında budanabilir olma özellikleri ile geçirimsiz çit formlarında da başarılıdır. Bu çalışmada amacımız, estetik ve fonksiyonel özelliklere sahip olan bu bitkinin çelikle üretim ile çoğaltılarak peyzaj mimarlığı bitkilendirme tasarımlarında kullanımlarının teşvik edilmesidir. Bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…This outcome was in line with the research's findings that hormone administration promoted rooting (Atıcı, 1999;Şekeroğlu et al, 2001;Ilgın and Bulat, 2001;Uysal et al, 2010;Pulatkan et al, 2018;Sarı and Kaçar, 2019). Additionally, Pulatkan et al (2018) observed that when IBA, IAA, and NAA hormones were provided at dosages of 0, 1000, 3000, 5000, and 8000 ppm upon rooting of Berberis thunbergii, the largest number of roots occurred at the dose of 3000 ppm of each hormone.…”
Section: Black Sea Journal Of Agriculturesupporting
confidence: 85%
“…This outcome was in line with the research's findings that hormone administration promoted rooting (Atıcı, 1999;Şekeroğlu et al, 2001;Ilgın and Bulat, 2001;Uysal et al, 2010;Pulatkan et al, 2018;Sarı and Kaçar, 2019). Additionally, Pulatkan et al (2018) observed that when IBA, IAA, and NAA hormones were provided at dosages of 0, 1000, 3000, 5000, and 8000 ppm upon rooting of Berberis thunbergii, the largest number of roots occurred at the dose of 3000 ppm of each hormone.…”
Section: Black Sea Journal Of Agriculturesupporting
confidence: 85%
“…In a study carried out by Pulatkan et al, (2018) on Berberis thunbergii cuttings, the lowest value in concentrated hormone treatments was obtained in 1000 ppm NAA application, while the highest value was obtained in 3000 ppm NAA application.…”
Section: Discussionmentioning
confidence: 95%